FEATURES OF TESTS AND TEST CONTROL OF ACADEMIC ACHIEVEMENTS IN PHYSICS - Bosin, Mark; Rykova, Larysa; Broslavska, Halyna (Physical and Mathematical Education, 2025)
Formulation of the problem. The assessment of students’ academic performance constitutes an integral component of the educational process, with testing being one of the most widely applied forms of assessment. The principal research objective of this study is to address specific challenges arising in the development of test items in physics education, particularly in certain domains that necessitate deviations from conventional testing approaches. The analysis of such deviations, combined with the demonstration of their practical implementation, represents the core problem explored in this work. Materials and methods. The materials underpinning this research comprise both the scholarly contributions of colleagues and the authors’ own pedagogical experience in teaching physics across several higher education institutions in Kharkiv. A significant portion of the authors’ materials was subjected to statistical analysis. Additionally, the careful examination of selected chapters from seminal works authored by eminent physicists — such as Albert Einstein, Max Planck, Erwin Schrödinger, and Louis de Broglie — proved highly valuable. The primary methodological framework employed in this study involves a comprehensive analysis of research on pedagogical testing in physics, as well as the systematic application of the authors’ conclusions, derived from extensive teaching practice. Results. The distinctive features encountered in the construction of physics test items are intrinsically linked to the nature of the discipline itself. These features are determined by two principal factors. The first concerns the fact that within many branches of physics, numerous phenomena exhibit dual or even multiple interpretations (e.g., wave–particle duality, non-relativistic and relativistic formulations). Such cases pose significant difficulties for test design and necessitate the adoption of non-standard approaches. The second factor lies in the absence of rigorously established theories for certain experimentally discovered phenomena, although well-founded hypotheses exist to account for them. Accordingly, formulating test tasks in such instances requires innovative strategies. Drawing upon the authors’ experience, the most effective approach involves presenting each test item as a structured sequence of smaller, interrelated sub-tasks. This technique has demonstrated considerable pedagogical efficacy. Conclusions. In situations where physical objects or phenomena are described by multiple, mathematically consistent theoretical frameworks, both the structure and the content of test items depend on the number of theoretical approaches considered and the complexity of the mathematical relationships between them. Conversely, when physical objects or phenomena are characterized not by established theories but by provisional hypotheses, the structure of test items should reflect the number of such hypotheses and the experimental evidence underlying them. In this case, the content must be designed to enable the assessment of the relative plausibility of each hypothesis. As indicated by the authors’ teaching experience, this type of testing provides a highly accurate measure of students’ comprehension of complex physical phenomena. Furthermore, analyzing test results often helps instructors refine and improve their instructional methodologies.